Effect of Dietary Sodium Modulation on Pig Adrenal Steroidogenesis and Transcriptome Profiles. Issue 6 (December 2020) - Vohra, Twinkle; Kemter, Elisabeth; Sun, Na; Dobenecker, Britta; Hinrichs, Arne; Burrello, Jacopo; Gomez-Sanchez, Elise P.; Gomez-Sanchez, Celso E.; Wang, Jun; Kinker, Isabella-Sabrina; Teupser, Daniel; Fischer, Konrad; et al.
Abstract : Primary aldosteronism is a frequent form of endocrine hypertension caused by aldosterone overproduction from the adrenal cortex. Regulation of aldosterone biosynthesis has been studied in rodents despite differences in adrenal physiology with humans. We, therefore, investigated pig adrenal steroidogenesis, morphology, and transcriptome profiles of the zona glomerulosa (zG) and zona fasciculata in response to activation of the renin-angiotensin-aldosterone system by dietary sodium restriction. Six-week-old pigs were fed a low- or high-sodium diet for 14 days (3 pigs per group, 0.4 g sodium/kg feed versus 6.8 g sodium/kg). Plasma aldosterone concentrations displayed a 43-fold increase ( P =0.011) after 14 days of sodium restriction (day 14 versus day 0). Low dietary sodium caused a 2-fold increase in thickness of the zG ( P <0.001) and an almost 3-fold upregulation of CYP11B ( P <0.05) compared with high dietary sodium. Strong immunostaining of the KCNJ5 (G protein-activated inward rectifier potassium channel 4), which is frequently mutated in primary aldosteronism, was demonstrated in the zG. mRNA sequencing transcriptome analysis identified significantly altered expression of genes modulated by the renin-angiotensin-aldosterone system in the zG (n=1172) and zona fasciculata (n=280). These genes included many with a known role in the regulation of aldosterone synthesis and adrenal function. The most highly enriched biological pathways in the zG were related to cholesterol biosynthesis, steroid metabolism, cell cycle, and potassium channels. This study provides mechanistic insights into the physiology and pathophysiology of aldosterone production in a species closely related to humans and shows the suitability of pigs as a translational animal model for human adrenal steroidogenesis. Abstract : Supplemental Digital Content is available in the text.